Hubungan Gaya Hidup dan Pola Makan dengan Kejadian Hipertensi pada Lansia di Desa Padang Timur - Emy Humairah; Hermin Manganan; Suaib B Suaib B (Mando Care Jurnal, 2026)
Hypertension is one of the most common non-communicable diseases among older adults and a major risk factor for cardiovascular disease. Physical activity, sleep, and dietary patterns are modifiable factors that may influence blood pressure control. This study aimed to analyze the association of physical activity, sleep duration, and dietary patterns with hypertension among older adults in Padang Timur Village, Campalagian District, Polewali Mandar Regency. A quantitative study with a cross-sectional design was conducted involving 62 adults aged ≥60 years selected using the total sampling technique. Data were collected using structured questionnaires on physical activity, sleep, and dietary patterns, followed by blood pressure measurements using a standardized manual sphygmomanometer. Data were analyzed using the Chi-square test with a significance level of p<0.05. Most participants had adequate physical activity (80.6%), adequate sleep (61.3%), and good dietary patterns (64.5%), while 87.1% were classified as hypertensive. Bivariate analysis revealed significant associations between physical activity (p=0.000), sleep (p=0.000), dietary patterns (p=0.001), and hypertension. The study concludes that physical activity, sleep, and dietary patterns are significantly associated with hypertension among older adults. These findings support the importance of healthy lifestyle interventions in community-based hypertension prevention and management.